The Existence of PT Jamsostek in Social Security Services For Workers with a Specific Time Work Agreement (PKWT) (Study at PT Jamsostek (Persero) Belawan Branch) - Jones Parapat (IHSA Institute, 2022)
The implementation of the social security program for workers based on a Specific Time Work Agreement (PKWT) in its implementation often does not work as expected which is able to provide protection and welfare / peace of mind for PKWT workers so that the authors are interested in raising this issue as a problem in the thesis. entitled